Diacryloyl Derivative of Mannitol – Synthesis and Application in Gelcasting of Al2O3-ZrO2 Composites - A. Antosik; E. Pietrzak; P. Wiecińska; D. Kubica; A. Sakowicz; N. Prokurat (Archives of Metallurgy and Materials, 2018)
The aim of research was the elaboration of the synthesis of new organic monomer applicable in gelcasting. The substance named 3,4-di-acryloyl-D-mannitol which contains two acryloyl groups and four hydroxyl groups in its molecule has been synthesized. The monomer has been then applied in the preparation of Al2O3-ZrO2 composites by gelcasting and subsequent sintering. Rheological properties of ceramic suspensions have been examined, as well as the properties of green and sintered bodies. SEM observations allowed to determine the distribution of zirconia grains in alumina matrix. Density, Vickers hardness and fracture toughness of ZTA composites have been measured. The new monomer, that is diacryloyl derivative of mannitol, is less sensitive to the oxygen inhibition than commonly used in gelcasting and commercially available 2-hydroxyethyl acrylate.